Nuevo reporte de Culex (Deinocerites) belkin Adames (Diptera: Culicidae) en Nicaragua - Morales Saldaña, J.
(En, Es)
Ilus., 3 ref.
Keywords: LEPIDOPTERA; DIPTERA; CULICIDAE; IDENTIFICACION; REGISTRO; NICARAGUA; DEINOCERITES